Digitalisation of Cultural Heritage and the Economics of Cultural Tourism: Transforming Preservation into Opportunity - Arias Aranda, Daniel (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
The digitalisation of cultural heritage represents one of the most significant transformations in contemporary cultural policy and tourism economics. This paper examines the intersection of digital technologies—including 3D scanning, virtual and augmented reality, artificial intelligence, and blockchain—with the preservation, accessibility, and economic valorisation of cultural heritage. Drawing on case studies from major institutions such as the Louvre, the British Museum, and innovative projects like Rome’s Circo Massimo Experience, we analyse how digitalisation creates economic value across the complete tourist journey: from pre-visit inspiration through on-site enhancement to post-visit engagement. The paper addresses the fundamental tension between heritage as a preservation cost and heritage as an economic opportunity, arguing that digital technologies offer solutions that simultaneously increase revenue, expand accessibility, and reduce physical strain on fragile sites. However, significant challenges remain, including the digital divide, technological obsolescence, questions of authenticity, and ethical considerations regarding ownership and representation. We conclude with a framework of principles for responsible digital heritage development and recommendations for cultural institutions seeking to navigate this transformation.